Penerapan Model Hybrid learning pada Pemahaman Siswa di SMP Negeri 1 Kota Bogor - Rudie Sulaeman (LPPM Institut Nasional Laa Roiba Bogor, 2023)
This study aims to determine the hybrid learning model on student understanding at SMP Negeri 1 Bogor City. A qualitative research method with a field study approach is the method used in this research. The results of the study stated that the use of hybrid learning in learning was a way out of the problems of learning that had been carried out, namely online as a whole. Hybrid learning supports and assists students in overcoming online learning, because in online learning there are many obstacles from the internet network, quota crisis, and students must continue to stare at the cellphone or laptop screen during learning. Problems that occur, it is necessary to hold a way to solve these, namely by implementing a hybrid learning model, rearranging learning hours, and giving students the freedom to get additional material via the internet. Therefore, the existence of a hybrid learning model makes students more active and easy to accept learning because of direct meetings and communication with teachers at school. The conclusion that can be drawn is that the hybrid learning model helps overcome student problems due to distance learning so that the activities and knowledge of students can be well observed by the teacher. Keywords: Application; Hybrid learning; Comprehension